The Concept of Monotheistic Humans Privileges in the Perspective of Muhammad bin Abdul Wahhab - Delavia Andrea Fererli; Efendi Efendi (Islamic Thought Review, 2023)
People do not often realize that humans who believe in (monotheism) will get privileges from Allah SWT. The matter makes today’s people less interested in tawhid. As a result, various deviations occur in the midst of Muslims’ life, such as a spiritual crisis which indicates that there has been a mistake in human perspective. This article explains what privileges will be obtained by monotheistic humans according to Muhammad bin Abdul Wahhab. This study used the literature or document study method in qualitative research with interpretation analysis techniques. The data used are primary and secondary. The primary data comes from the writings of Muhammad bin Abdul Wahhab. Then, secondary data is relevant literature to Muhammad bin Abdul Wahhab. According to him, the privileges obtained by monotheistic humans are; monotheism eradicates sins, and whoever practices monotheism will enter heaven and get peace of heart and soul.  These findings can have implications for humans who do not practice monotheism, do not believe, or are unaware of the privileges that humans will gain.